Barry Velleman, My Dear Sir. Mary Mann’s Letters to Sarmiento (1865- 1881). Buenos Aires, ICANA, 2001, 352 pp. - Casiraghi de Pryor, Florencia (2003)
Fil: Casiraghi de Pryor, Florencia. Investigador independiente; Argentina